Systemic and Disease-Specific Risk Factors in Vascular Dementia: Diagnosis and Prevention - Jaul, Efraim; Meiron, Oded (Frontiers in Aging Neuroscience, 2017)
In order to prevent the onset of vascular dementia (VaD) in aging individuals, it is critical to detect clinically relevant vascular and systemic pathophysiological changes to signal the onset of its preceding prodromal stages. Identifying behavioral and neurobiological markers that are highly sensitive to VaD classification versus other dementias is likely to assist in developing novel preventive treatment strategies that could delay the onset of disruptive psychomotor symptoms, decrease hospitalizations, and increase the quality of life in clinically-high-risk aging individuals. In light of empirical diagnostic and clinical findings associated with VaD pathophysiology, the current investigation will suggest a few clinically-validated biomarker measures of prodromal VaD cognitive impairments that are correlated with vascular symptomology, and VaD endophenotypes in non-demented aging people. In prodromal VaD individuals, distinguishing VaD from other dementias (e.g., Alzheimer's disease) could facilitate specific early preventive interventions that significantly delay more severe cognitive deterioration or indirectly suppress the onset of dementia with vascular etiology. Importantly, the authors conclude that primary prevention strategies should examine aging individuals by employing comprehensive geriatric assessment approach, taking into account their medical history, and longitudinally noting their vascular, systemic, cognitive, behavioral and clinical functional status. Secondary prevention strategies may include monitoring chronic medication as well as promoting programs that facilitate social interaction and every-day activities.